SOSIALISASI DAN PENDAMPINGAN SISTEM KEMAMPUAN TELUSUR (TRACEABILITY) UNTUK MENDUKUNG SISTEM PRODUK JAMINAN HALAL (SJPH) DI UD SOFIA COOKIES, SURABAYA - Juhariyah Juhariyah; Jariyah Jariyah; Hadi Munarko; Sri Winarti; Kindriari Nurma Wahyusi (Fakultas Teknik, Universitas Bangka Belitung, 2023)
Indonesia is the country with the largest muslim population in the world, so it is a domestic market for halal products. The Micro, Small, and Medium Enterprises (MSMEs) sector is the driving agent of the halal value chain. UD Sofia Cookies is one of the MSMEs in Surabaya that produces various pastries or cookies. UD Sofia Cookies already has a PIRT distribution permit and is currently making efforts to register halal certification. One of the criteria for the halal assurance system (SJH) from LPPOM MUI is the traceability system. Traceability is an aspect needed to ensure the halalness of halal product materials starting from the purchase of raw materials, production processes, to logistics and product distribution. Traceability can increase consumer confidence as well as a requirement for food safety, health, and authenticity of food products. UD Sofia cookies have not implemented a halal traceability system, so they require socialization and assistance in implementing a halal traceability system. The results of socialization and assistance show that UD Sofia Cookies employees have been able to implement a halal traceability system. So that UD Sofia Cookies can proceed to the next stage to register a halal certificate.